2001
DOI: 10.1093/jn/131.11.2963
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat Content Can Be Predicted In Vivo in Mice Using a Modified Dual-Energy X-Ray Absorptiometry Technique

Abstract: The introduction of transgenic mice as animal models in medical research has increased the need for methods to study the phenotype of mice. The aim of the present study was to develop and evaluate a method for in vivo prediction of fat content in living mice. We combined a modified dual-energy X-ray technique with an image analysis procedure. This combined procedure calculates the percentage of fat area, defined as the percentage of the total area of the mice consisting of >50% fat. A high correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 6 publications
2
35
1
Order By: Relevance
“…Clearly the results from the present study differ from that of Sjögren et al (8). The reason for the differences between studies is not clear.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Clearly the results from the present study differ from that of Sjögren et al (8). The reason for the differences between studies is not clear.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, we concluded that 8 mm/s was a good trade-off between reproducibility and reasonable scan times. Sjögren et al (8) did not give any information on the DXA measurements (e.g., scan speed, resolution, histogram averaging method) nor did they provide data to substantiate their claim. Thus, if scan speeds in excess of 8 mm/s were used, that may explain their negative findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of body composition. Analysis of body fat and lean body mass (LBM) in IL-1RI Ϫ/Ϫ and wild-type controls was performed by dual-energy X-ray absorptiometry (DEXA) with the Norland (Fort Atkinson, WI) pDEXA Sabre and the Sabre Research software (version 3.9.2), as described (17,18). The crown-rump length was measured on the same DEXA scans as the body fat and LBM and was defined as the distance between the crown of the skull to a point located in the middle line of the two caput femoris.…”
Section: Methodsmentioning
confidence: 99%
“…At week 15, body composition was measured in mice anesthetized with isofluorane (Baxter, Deerfield, IL, USA) using a Lunar PIXImus densitometer (Lunar Corp, Madison, WI, USA) as previously described (26).…”
Section: Dual Energy X-ray Absorptiometry (Dxa)mentioning
confidence: 99%